Musical segmentation - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
This case study asks readers to consider the intersection of international marketing practices with music in various cultural contexts. Different musical forms are associated with different market segments, allowing for a multitude of different international marketing opportunities.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Musical Segmentation. In International marketing (pp. 115-116). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Market segmentation -- Case studies; Export marketing -- Case studies; Consumers' preferences -- Case studies; Music audiences -- Case studies